Blood Biochemical, Hormonal and Mineral Status of Cyclic, Acyclic, Endometriotic and Pregnant Crossbred Cows - Patel, Chirag I; Dhami, AJ; Panchal, MT; Sarvaiya, NP; Shah, SV (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A study was carried out on infertile (acyclic and endometriotic) crossbred cows under field and normal cyclic (all 4 phases of cycle) as well as pregnant (3, 6, 9 month) crossbred cows of University farm to evaluate the plasma progesterone (P4) and estradiol (E2) hormones by RIA, and plasma total protein, cholesterol, calcium and phosphorus concentrations by using assay kits on chemistry analyzer. The mean progesterone levels in cows during the diestrus phase and in pregnancy were significantly (p <0.05) higher than those during proestrus, estrus, metestrus, anestrus, and endometritis status. At six month of gestation, the mean P4 level was significantly (p <0.05) higher than at early or late gestation. The mean E2 values at estrus and 9th month of gestation were highest (p <0.01) as compared to another status. The mean plasma total protein and cholesterol levels were significantly (p <0.05) lower during six and nine months of pregnancy than during cyclic and acyclic stages. The cholesterol profile of all three stages of pregnancy and endometriotic cows were statistically similar, though distinctly low at 9 month of pregnancy. Plasma levels of P4 and E2 thus correlated with the physiological and clinical status of cows, while cholesterol levels reflected steroidogenic status. The mean plasma calcium and inorganic phosphorus concentrations of cyclic, acyclic, pregnant and endometriotic cows, however, did not differ significantly.